A literature review of the effects of computer input device design on biomechanical loading and musculoskeletal outcomes during computer work. - Garza, J. L. Bruno; Young, J. G. (Work, 2015)
BACKGROUND: Extended use of conventional computer input devices is associated with negative musculoskeletal outcomes. While many alternative designs have been proposed, it is unclear whether these devices reduce biomechanical loading and musculoskeletal outcomes. OBJECTIVE: To review studies describing and evaluating the biomechanical loading and musculoskeletal outcomes associated with conventional and alternative input devices. METHODS: Included studies evaluated biomechanical loading and/or musculoskeletal outcomes of users' distal or proximal upper extremity regions associated with the operation of alternative input devices (pointing devices, mice, other devices) that could be used in a desktop personal computing environment during typical office work. RESULTS: Some alternative pointing device designs (e.g. rollerbar) were consistently associated with decreased biomechanical loading while other designs had inconsistent results across studies. Most alternative keyboards evaluated in the literature reduce biomechanical loading and musculoskeletal outcomes. Studies of other input devices (e.g. touchscreen and gestural controls) were rare, however, those reported to date indicate that these devices are currently unsuitable as replacements for traditional devices. CONCLUSIONS: Alternative input devices that reduce biomechanical loading may make better choices for preventing or alleviating musculoskeletal outcomes during computer use, however, it is unclear whether many existing designs are effective.